Pengaruh Aromaterapi Peppermint Terhadap Mual Muntah Ibu Hamil Trimester I Di Wilayah Kerja Pmb Hadijah Kabupaten Tanggerang Provinsi Banten - Alifah, Siti Alifah; Sugiantini, Titin Eka (Jurnal Keperawatan Muhammadiyah, 2024)
Nausea and vomiting (emesis gravidarum) are normal in pregnant women but if nausea and vomiting occur >10 times a day, it can disrupt nutritional balance, electrolyte fluids, and can affect the general condition so that if vomiting increases to hyperemesis it can result in impaired fetal growth. The incidence of emesis gravidarum in pregnant women is 50-90%, while hyperemesis gravidarum reaches 10-15% in Banten Province from the number of pregnant women who are 182,815 people in first trimester pregnancy, nausea in pregnancy can be overcome by using complementary therapies, among others with aromatherapy. The purpose of the study was to determine the effect of peppermint aromatherapy on nausea and vomiting in first trimester pregnant women in the work area of PMB Hadijah, Tanggerang Regency, Banten Province.Â Quantitative research, quasi-experiment research design or pseudo-experiment. The population was all pregnant women at BPM Khadijah, with a population of 32 mothers and 20 mothers were taken by purposive sampling with the object of TM I pregnant women who experienced nausea and vomiting. The research was conducted at BPM Hadijah, Tanggerang Regency, Banten Province in June 2023. Data collection using observation sheets. univariate and bivariate data analysis (independent t test).Â The results of the study showed that the average nausea vomiting before being given peppermint aromatherapy intervention was 8.90 after being given peppermint aromatherapy was 6.55. There is an effect of peppermint aromatherapy on nausea and vomiting in first trimester pregnant women in the work area of PMB Hadijah, Tangerang Regency, Banten Province with a P-value of 0.000. Suggestions for health workers can use peppermint aromatherapy as an SOP in reducing nausea and vomiting in pregnant women